The Impact of Changing to an Algorithm-Based Clostridioides difficile Test on the Decision to Treat Clostridioides difficile. (October 2020) - Dbeibo, Lana; Williams, Joy; Sadowski, Josh; Fadel, William; Winn, Vera; Webb, Douglas Houston; Kara, Areeba
Abstract : Background: Polymerase chain reaction (PCR) testing for the diagnosis of Clostridioides difficile infection (CDI) detects the presence of the organism; a positive result therefore cannot differentiate between colonization and the pathogenic presence of the bacterium. This may result in overdiagnosis, overtreatment, and risking disruption of microbial flora, which may perpetuate the CDI cycle. Algorithm-based testing offers an advantage over PCR testing as it detects toxin, which allows differentiation between colonization and infection. Although previous studies have demonstrated the clinical utility of this testing algorithm in differentiating infection from colonization, it is unknown whether the test changes CDI treatment decisions. Our facility switched from PCR to an algorithm-based testing method for CDI in June 2018. Objective: In this study, we evaluated whether clinicians' decisions to treat patients are impacted by a test result that implies colonization (GDH+/Tox−/PCR+ test), and we examined the impact of this decision on patient outcomes. Methods: This is a retrospective cohort study of inpatients with a positive C. diff test between June 2017 and June 2019. The primary outcome was the proportion of patients treated for CDI. We compared this outcome in 3 groups of patients: those with a positive PCR test (June 2017–June 2018), those who had a GDH+/Tox−/PCR+ or a GDH+/Tox+ test result (June 2018–June 2019). Secondary outcomes included toxic megacolon, critical care admission, and mortality in patients with GDH+/Tox−/PCR+ who were treated versus those who were untreated. Results: Of patients with a positive PCR test, 86% were treated with CDI-specific antibiotics, whereas 70.4% with GDH+/Tox+ and 29.25% with GDH+/Tox−/PCR+ result were treated ( P < .0001). Mortality was not different between patients with GDH+/Tox−/PCR+ who were treated versus those who were untreated (2.7% vs 3.4%; P = .12), neither was critical care admission within 2 or 7 days of test result (2% vs 1.4%; P = .15) and (4.1% vs 5.4%, P = .39), respectively. There were no cases of toxic megacolon during the study period. Conclusions: The change to an algorithm-based C. difficile testing method had a significant impact on the clinicians' decisions to treat patients with a positive test, as most patients with a GDH+/Tox−/PCR+ result did not receive treatment. These patients did not suffer more adverse outcomes compared to those who were treated, which has implications for testing practices. It remains to be explored whether clinicians are using clinical criteria to decide whether or not to treat patients with a positive algorithm-based test, as opposed to the more reflexive treatment of patients with a positive PCR test. Funding: None Disclosures: None